2010
DOI: 10.1038/ijo.2010.13
|View full text |Cite|
|
Sign up to set email alerts
|

The anti-angiogenic herbal composition Ob-X inhibits adipose tissue growth in obese mice

et al.

Abstract: Objective: The growth and development of adipose tissue are thought to be associated with angiogenesis and extracellular matrix remodeling. As the composition of the herbal extract called Ob-X has been shown to have both anti-angiogenic and matrix metalloproteinase (MMP)-inhibiting activities, we hypothesized that growth of adipose tissue can be regulated by Ob-X. Materials and methods: The effects of Ob-X on angiogenesis and extracellular matrix remodeling were measured using in vitro and ex vivo assays. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
5
23
0
Order By: Relevance
“…We find that endostatin inhibits adipogenesis by the mechanism of impairing Sam68-mediated alternative splicing of mTOR and reducing the activity of the mTORC1 pathway. In addition, we demonstrate that the well-known antiangiogenic activity of endostatin also contributes to its antiobesity effect, which is consistent with previous observations that several angiogenesis inhibitors, including angiostatin and TNP-470, prevent obesity in mice (13,14).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find that endostatin inhibits adipogenesis by the mechanism of impairing Sam68-mediated alternative splicing of mTOR and reducing the activity of the mTORC1 pathway. In addition, we demonstrate that the well-known antiangiogenic activity of endostatin also contributes to its antiobesity effect, which is consistent with previous observations that several angiogenesis inhibitors, including angiostatin and TNP-470, prevent obesity in mice (13,14).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to tumor tissue, WAT development in physiological and pathological contexts is accompanied by the formation of vascular networks (12,13), and several angiogenesis inhibitors have been reported to exert an antiobesity effect by inhibiting angiogenesis in adipose tissue (13,14). As a result of these studies, adipose tissue angiogenesis has a great potential as a therapeutic target for obesity and metabolic diseases (12).…”
mentioning
confidence: 99%
“…In agreement with reductions in body weight gain, Ob-X significantly reduced mesenteric fat mass by 15% in obese ob/ob mice. Our previous study showed that treatment of high-fat diet-induced obese mice with Ob-X for 12 weeks reduced visceral fat mass by 38% (Kim et al, 2010). Lijnen et al (2002) also reported that administration of TNP-470 for 12 weeks induced decreases in visceral fat mass in highfat diet-fed mice.…”
Section: Controlmentioning
confidence: 93%
“…It is suggested, therefore, that adipose tissue growth is angiogenesis-dependent and may be inhibited by angiogenesis inhibitors. Recently, we demonstrated that the anti-angiogenic dietary supplement Ob-X reduces adipose tissue mass and suppresses obesity by inhibiting angiogenesis [7]. …”
Section: Introductionmentioning
confidence: 99%